0912 The mysterious case of a dangerous dreamless sleep and how to cure it …. (1st December 2017) - Bonello, Michael; Jacob, Anu; Ellul, Mark Alexander; Jefferson, Samantha; Barker, Erandi; Parker, Robert; Alusi, Sundus H
Abstract : A 45-year-old man presented with a one-year history of confusion and change in sleep pattern. He was obese and in ventilatory failure with episodes of stridor, sleep disordered breathing, central cyanosis, dysarthria, dysphagia myoclonus and gait ataxia. EEG showed generalised slowing and CSF was inflammatory. Polysomnography revealed increased sleep drive but reduced NREM sleep and a complete absence of REM sleep. An extensive workup for an autoimmune cause was negative and no cancer was identified. In view of inflammatory CSF, he was treated with IVIG, steroids, plasma exchange and cyclophosphamide, with dramatic improvement. Serum and CSF antibodies to IgLON5 returned positive. HLA genotyping confirmed HLA-DQB1*05:01 and HLA-DRB1*10:01 alleles. The few cases in literature (<20) of this recently described autoimmune syndrome have all been fatal, but our patient maintains improvement at 2 years from onset. His behaviour has normalised and sleep pattern improved with the return of dreams, and resolution of neck pain and dysphagia. This is the first report of a recently recognised rare autoimmune disorder in the UK that has shown sustained improvement with treatment suggesting at least a proportion of cases responds to treatment.